2014
DOI: 10.4161/21645515.2014.972155
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pneumococcal vaccination among an urban elderly population in China

Abstract: Objectives: To investigate the coverage of the 23-valent pneumococcal polysaccharide vaccine (23-PPV) in the Chinese urban elderly population and to understand the attitudes, knowledge and beliefs of this population toward the 23-PPV vaccination. Methods: A cross-sectional approach was employed to survey the willingness of this population to receive the 23-PPV vaccination. Two thousand 9 hundred 2 six subjects over the age of 60 y were enrolled via a multistage random sampling method from the urban community p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
4
18
1
Order By: Relevance
“…The reason for our finding was presumed to be as follows: participants who had this type of perception held a belief that the consequences of disease could possibly have a great impact not only clinically (death, disability, and pain) but also socially (effects on work, family life, and social relationships); consequently, these people were more likely to receive vaccination. An association between an individual’s perception and pneumococcal vaccination has been reported in some studies [ 23 , 27 , 28 ], supporting our result.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reason for our finding was presumed to be as follows: participants who had this type of perception held a belief that the consequences of disease could possibly have a great impact not only clinically (death, disability, and pain) but also socially (effects on work, family life, and social relationships); consequently, these people were more likely to receive vaccination. An association between an individual’s perception and pneumococcal vaccination has been reported in some studies [ 23 , 27 , 28 ], supporting our result.…”
Section: Discussionsupporting
confidence: 93%
“…Receiving influenza vaccination at least once in the previous three seasons also had a strong association with pneumococcal vaccination (aOR 3.94, 95% CI 1.70–9.13, p = 0.001). An association between influenza vaccination history and pneumococcal vaccination have been reported previously [ 23 , 25 , 27 , 28 ]. Vaccination itself is a fundamental and important measure to prevent disease.…”
Section: Discussionmentioning
confidence: 71%
“…20 Similar findings of the association between influenza vaccination and pneumococcal vaccination have also been noted. [21][22][23] In addition, this study found that adults with more outpatient hospital visits, more doctor office visits, and more pharmacy visits with prescription drugs filled were more likely to receive the vaccine. This could be because patients with more healthcare encounters were more likely to be informed about the vaccine or be more aware of the recommendation for the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…6 Another Chinese study found that few subjects received suggestions from physicians (7.73%), and only 1.23% of the subjects had previously received the 23-PPV vaccination. 7 Inactivated vaccines that are recommended in patients with autoimmune diseases (ARD). Influenza vaccination and pneumococcal vaccine are routinely recommended to adults using immunosuppressive agents as influenza and pneumonia are among the most common and life-threatening infections.…”
Section: Introductionmentioning
confidence: 99%